Facial Emotion Recognition through Fuzzy Systems - et. al., Anju Das, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper provides a logical framework for understanding. The program consists of a photo processing section followed by an emotional awareness section. In the image processing phase, the face and face of the subject eyes and mouth are removed. Next, appropriate points for use should be underlined in each facial expression. In the visual field, sensory points are used for fuzzify and determine the magnitude of the various facial actions. This power is used to make the concept of the topic stand out. Japanese Women's Face Database used to evaluate program performance which resulted in a full recovery of 78.8%.